The Role of Women in Livestock Farming: Challenges and Opportunities (Indian Journal of Animal Production and Management, 2025)
Women are actively involved in livestock farmingpractices in rural India. They have both emotional and economical association with livestock. Most women are engagedin care and management of livestock such as feeding, milking and cleaning of shed.Disposal and use ofwaste material and dung from the shed is also performed by the women. Their immense contribution in livestock farming provides financial independence and better social status. Their hard and dedicated works endow rural livelihood, and pledge food security. It ensures full time employment and dispenses woman empowerment in the society. Nevertheless,women frequently encounter obstaclesin livestock farming, affecting theproduction. Social customand gender-based discrimination render limited access to markets, veterinary care, education, financial freedom, and use of land. Limited decision making power of a woman appeared as a great hindrance in socio-economical and sustainable development of a country.
Keywords: Livestock farming; Women empowerment; Sustainable development.